STRATEGI PENGEMBANGAN EKOWISATA BERBASIS EKONOMI LOKAL DALAM RANGKA PROGRAM PENGENTASAN KEMISKINAN DI WILAYAH KABUPATEN MALANG - Satria, Dias (Journal of Indonesian Applied Economics, 2009)
In  the  era of  sustainable  development,  alternative  and  sustainable  tourism havebecome a great  concern  for  local government. Sempu  Island which  is  located  inKabupaten Malang is one of  the interesting cases on how the Ecotourism conceptcould be combined to the local economic development and conservation issues. Theaims of this paper are to gather information about the picture of Ecotourism practicesin Sempu Island. Furthermore, it will formulate the strategic way to make ecotourismwork well to the development of the local society.Keywords: Sustainable development, ecotourism, Sempu Island and local economy.